A Simple and Compact MR-Compatible Electromagnetic Vibrotactile Stimulator - Jiang, Xinjian; Wang, Yueqian; Li, Xiaojin; Wang, Liping; Zhou, Yong-Di; Wang, Huimin (Frontiers in Neuroscience, 2020)
We have developed a low-cost electromagnetic vibrotactile stimulator that uses the magnetic field of an MR scanner as a permanent magnet to power a vibrating motor. A simple variable current power supply is controlled by software using a USB data acquisition controller. In our study, the function of our novel stimulator was verified in a vibration frequency discrimination working memory task, in which various ranges of frequencies and amplitudes are delivered in MRI scanner. Furthermore, our fMRI study revealed activations of the primary and secondary somatosensory cortices during the perception of tactile stimulation. Therefore, the new designed electromagnetic vibrotactile stimulator is capable of generating various frequencies of tactile stimuli and represents a powerful and useful tool for studying somatosensory functions with fMRI.